PEMANFAATAN ZEOLIT UNTUK PENURUNAN COD DAN BOD LIMBAH PENGOLAHAN KULIT - Cahya Widiyati (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2013)
Leather is one of the semi-finished products that contribute to the export of non-oil commodities. In general, leather processing wastewater containing germs, dirty-colored, foul- smelling and containing COD, BOD5 and suspended solids are high. One of the adsorbent which has a large adsorption capacity is the natural zeolite. Natural zeolite adsorption capability increases when first activated zeolite. Zeolites can reduce pollutants in the form of cations and anions in wastewater so it can reduce COD and BOD5 waste leather processing. The purpose of this study to determine the effect of HCl concentration of activating zeolites and zeolite-activated heavy influence for BOD5 and COD reduction. The method used is laboratory-scale experiments. Activation 150 grams zeolite - 40 + 60 mesh by heating 2500C and the addition of 0.1 N HCl acid, 0.15 N, 0.2 N and 0.25 N. Zeolites are separated and dried in an oven. Weight activated zeolite 5 grams, 10 grams, 15 grams and 20grams. Mixing zeolite and 100 cc leather processing waste electrical stirrer 150 rpm for 30 minutes and then separated sediment. The filtrate was tested in COD and BOD5 waste leather processing. Do also test COD and BOD 5 without zeolite. COD tests using a COD reactor and BOD5 tests using Winkler method. The results showed that the zeolites were activated by heating 2500 C, 0.15 N HCl and weight of 20 grams of activated zeolite an optimum condition to reduce COD and BOD5 BOD5 decreased 96.67% to the value of 105 mg / l and COD reduction reached 92.23% with a value of 335.36 mg /l. Zeolite results of this study can be used for leather industry because zeolites are widely available in Indonesia and can to reduce levels BOD5 and COD leather processing waste.